An investigator-blind randomized controlled trial comparing effectiveness, safety of levocetirizine and bepotastine in chronic urticaria - Amrita Sil; Sufiur Rahaman; Nasiruddin Mondal; Sk Shahriar Ahmed; Dhiman Tarafdar; Aparesh Chandra Patra; Sudipta Roy; Nilay Kanti Das (Wolters Kluwer Medknow Publications, 2021)
Introduction: Chronic urticaria is common and distressing dermatosis where the search for newer agents with improved effectiveness and tolerability profile is a felt need. Bepotastine, a second-generation antihistamine, with added effect on suppression of eosinophil migration has a prospect in the management of chronic urticaria. Aims: To assess and compare effectiveness and safety of bepotastine versus levocetirizine in chronic urticaria. Materials and Methods: Single-center, investigator-blind, randomized, active-controlled, parallel-group phase IV trial (CTRI REF/2018/04/019692) conducted on adult patients of chronic urticaria of either sex. Patients were randomized into receiving either bepotastine besilate 10 mg tablet twice daily or levocetirizine 5 mg tablet once daily with fortnightly follow-up for 6 follow-up visits after thebaseline evaluation. The primary outcome measures were Urticaria Activity Score 7 (UAS7) and Urticaria Total Severity Score (TSS). Routine hematological, biochemical tests, treatment-emergent adverse events were monitored for safety. Results: Thirty patients in the bepotastine group and 29 patients in the levocetirizine group were analyzed by modified-intention-to-treat criteria. The study groups were comparable at the baseline with respect to the severity of chronic urticaria. UAS7 and TSS reduced significantly (P < 0.001, Friedman's ANOVA) in both treatment groups from 1st follow-up visit and 2nd follow-up visits (P < 0.05, Post Hoc Dunn's test) At the test-of-cure visit, UAS7 (5.13 ± 8.21 vs 7.48 ± 8.96) and TSS (5.10 ± 4.06 vs 7.07 ± 4.48) were less with bepotastine than levocetirizine although not statistically significant (P = 0.188 and 0.073, respectively, Mann-Whitney U test). Sedation during daytime was found to be significantly more (P < 0.001, Fischer's exact test) with levocetirizine than bepotastine (73.3% vs 17.2%). Conclusion: Bepotastine is comparable to levocetirizine with respect to its effectiveness with an edge in terms of side-effect (sedation during day time); thus, it offers a new therapeutic option in chronic urticaria.